DESKRIPSI PELAKSANAAN PEMBELAJARAN TEMATIK MENGGUNAKAN SISTEM DARING GURU KELAS V DI SD NEGERI 31 PONTIANAK BARAT - Rana Raihana; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe research aims to describe the thematic learning problems using the fifth grade teacher's online system. The research method is a descriptive method with a qualitative approach. The participants in this study were class VA teachers and class VB teachers as informants and respondents totaled 24 people consisting of 6 class VA students, 6 VB class students, 6 VA class parents and 6 VB class parents. totaling 6 people. The research instrument is the human instrument. Data collection techniques are interviews, questionnaires/questionnaires, documentation studies. The data analysis technique used is the Miles and Huberman model. The results of the research teachers have made preparations for preparing lesson plans, learning materials, learning methods, determining the type of learning media, participating in online learning training using the WhatsApp application, Google Meet, and learning videos made by themselves or adopted from Youtube. The teacher's constraints are during the process of delivering learning materials, the process of interaction with students in the learning process, obstacles during evaluation and learning objectives, and when managing teaching materials. the teacher's solution is to attend seminars or training on information technology and learn from teachers in schools who have broader insights, provide guidance to children in groups or individually.Keywords: Description, Implementation of Thematic Learning, Online System